Improved C45 performance with gain ratio for credit approval dataset - Ivandari Ivandari; M Adib Al Karomi; Much. Rifqi Maulana (JAICT, 2022)
Abstract— People's shopping behavior has undergone many changes after the COVID-19 pandemic. Many people have switched to using the marketplace to make buying and selling transactions. The payment process in the marketplace is relatively easy, especially when using a credit card. The increase in demand for credit must be addressed better by financial providers to minimize bad loans. The best thing in minimizing bad credit is to be more selective in choosing credit customers. Data mining is a field that can study old data to become new knowledge in the future. In data mining, the classification of bad credit customers is mostly done. One of the algorithms that excels in handling credit approval datasets is C45. The C45 model is widely used because it has an output decision tree that is easier to understand in human language. The number of data attributes can affect the performance of the algorithm. Feature selection is a form of attribute reduction to improve data quality and improve classification algorithm performance. Gain ratio is the development of information gain and is the best feature selection model and is widely used by researchers. This study performs a classification using C45 and uses a gain ratio for the selection of credit approval data features. By using the gain ratio, the accuracy of the C45 classification algorithm increased from the previous 94.12% to 95.29%.